2017
DOI: 10.1115/1.4037692
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Effect of Suction Chamber Angle on the Entrainment of Passive Fluid in a Steam Ejector

Abstract: In this experimental study, the impact of suction chamber angle (SCA) on the entrainment ratio of a steam ejector refrigeration system (ERS) of 700 W was investigated. The basic dimensions of the ejector were derived from the compressible fluid flow equations using matlab. The system was tested with six different SCAs with various operating conditions, and its performance was analyzed. It is inferred that the entrainment of passive fluid from the evaporator is the strong function of the SCA. For all the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…They observed that the coefficient of performance declined with the decrease of the diameter of the constant area when fixed the nozzle exit position. Ramesh and Sekhar [16] conducted the experimental measurements to investigate the effect of six suction chamber angles on the entrainment ratio of a steam ejector. They found that the increasing suction chamber angle from 0° to 12° improves the entrainment ratio and above that the performance decreases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the coefficient of performance declined with the decrease of the diameter of the constant area when fixed the nozzle exit position. Ramesh and Sekhar [16] conducted the experimental measurements to investigate the effect of six suction chamber angles on the entrainment ratio of a steam ejector. They found that the increasing suction chamber angle from 0° to 12° improves the entrainment ratio and above that the performance decreases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The COP can be rewritten after a series of calculations by neglecting pump work using Equation (2) [31]:…”
Section: Numerical Analysis Of Flow Behaviour Inside the Steam Ejectormentioning
confidence: 99%
“…1 The entrainment ratio (ω), a ratio of induced mass to primary mass flow rate, is a global performance indicator of the ejector. To improve the performance of the ejector, many studies have been carried out to optimize geometrical parameters, 2,3 operating parameters, 4,5 ejector design approaches 68 and many more.…”
Section: Introductionmentioning
confidence: 99%